Detection of disease‐causing CFTR variants in state newborn screening programs. Issue 2 (25th October 2022) - McGarry, Meghan E.; Ren, Clement L.; Wu, Runyu; Farrell, Philip M.; McColley, Susanna A.
Abstract: Background: Newborn screening (NBS) algorithms for cystic fibrosis (CF) vary in the United State of America and include different cystic fibrosis transmembrane conductance regulator ( CFTR) variants. CFTR variant distribution varies among racial and ethnic groups. Objective: Our objectives were to identify differences in detection rate by race and ethnicity for CFTR variant panels, identify each US state detection rate for CFTR variant panels, and describe the rate of false‐negative NBS and delayed diagnoses by race and ethnicity. Methods: This is a cross‐sectional analysis of the detection rate of at least 1 CFTR variant for seven panels by race and ethnicity in genotyped people with CF (PwCF) or CFTR‐related metabolic syndrome (CRMS)/CFTR‐related disorders in CF Foundation Patient Registry (CFFPR) in 2020. We estimated the case detection rate of CFTR variant panels by applying the detection rate to Census data. Using data from CFFPR, we compared the rate of delayed diagnosis or false‐negative NBS by race and ethnicity. Results: For all panels, detection of at least 1 CFTR variant was highest in non‐Hispanic White PwCF (87.5%−97.0%), and lowest in Black, Asian, and Hispanic PwCF (41.9%−93.1%). Detection of at least 1 CFTR variant was lowest in Black and Asian people with CRMS/ CFTR ‐related disorders (48.4%−64.8%). States with increased racial and ethnic diversity have lower detection rates for all panels. Overall, 3.8% PwCF had a false‐negative NBS and 11.8% had a delayed diagnosis; Black, Hispanic, and mixed‐race PwCF were overrepresented. Conclusion: CFTR variant panels have lower detection rates in minoritized racial and ethnic groups leading to false‐negative NBS, delayed diagnosis, and likely health disparities.